THE EFFECT OF ENTREPRENEURSHIP EDUCATION AND FAMILY ENTREPRENEURSHIP ON STUDENT ENTREPRENEURSHIP INTENTION - Mawardi, Mukhammad Kholid; Sahputri, Rindi Ardika Melsalasa (Universitas Brawijaya, Indonesia, 2022)
This study examines the relationship between entrepreneurship education and students' intentions and tests students to moderate the effects of students' perceived experience and family entrepreneurial orientation, which can strengthen or weaken the effect of entrepreneurship education on intention. This study also evaluates why Indonesian students become entrepreneurs and the important contributing factors and barriers to doing so. Data were collected from 584 vocational students at an Indonesian state university. All tests, including descriptive statistics and ordinary least squares regression, were analyzed using Stata 15.0, which effectively analyzes extensive sample surveys. The results prove a higher level of entrepreneurial intention in students from families oriented and experienced in entrepreneurship. Our results also reveal that student experience and having friends who become entrepreneurs reduces entrepreneurial intentions, but the difference is not statistically significant. Despite expanding research on education and entrepreneurial intention, the relationship between perceived experience, family entrepreneurial orientation, and students' entrepreneurial intentions has not been studied adequately, especially in the Indonesian context. But the difference was not statistically significant.